Best Answer

2a*4b*(-3c) = ?

2 * 4 * -3 * a * b * c = ?

-24abc

Q: How do you simplify 2a times 4b times -3c?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6a²b - 12ab²

It is: 12b2

12b2 - 8b = 0 4b(3b-2) = 0 4b = 0 and 3b-2 = 0 4b = 0 and 3b = 2 b = 0 and 2/3

8b - 4b = 4b

Well if it is worded right then 4xb-1+(-4)+4b=4b-1-4+4b=4b+4b-1-4=8b-5

Related questions

2a + 4b

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

3b -1

2a-4b = -2

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

12bc - 4bd - 15xc + 5xd = 4b(3c - d) - 5x(3c - d) = (3c - d)(4b - 5x)

The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b

a=2b 4b=6c becomes 2b=3c a=3c

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

2a-3+4b-2a-b-3+5=3b-1